Patterns of pain medication use in older individuals with cardiovascular disease. (4th May 2018) - Kabbara, Wissam K.; Dimassi, Hani; Sheikh-Taha, Marwan
Abstract: Background: Pain is common in older adults and clinicians are often faced by many challenges when selecting appropriate treatment due to age-related changes in pharmacokinetics, pharmacodynamics, increased comorbidities, and polypharmacy. Methods: This study assessed the patterns of pain medications used at home among older adults admitted to the cardiology service in a tertiary care teaching center in the US from March to May 2016. A retrospective chart review was conducted where adults, 65 years of age or older, with cardiovascular diseases admitted to the cardiology service and taking at least one pain medication at home were studied. Results: Out of 404 patients who were admitted to the cardiology service, 228 (56.4%) were on at least one pain medication. Among the admitted patients, 64.2% of the females received at least one pain medication, as compared to 49% of the males ( p = 0.002). Participants had a mean age of 76.34 ± 7.43 years, and received a mean of 1.81 ± 0.83 pain medications. Neuropathic pain was the most common indication (33.4%), followed by arthritis (17.5%), and cancer (15.8%). The most commonly used pain medications were gabapentin/pregabalin 79 (34.6%), acetaminophen plus an opiate 78 (34.2%), opiates 56 (24.6%), tramadol 36 (15.8%), followed by non-selective NSAIDs 21 (9.2%). Twelve (5.3%) patients received duplication of pain medications, while 14 (5.7%) received an inappropriate combination of pain medications. Twenty-three patients (10.1%) received muscle relaxants in conjunction with pain medications, 20 of which are considered poorly tolerated by older adults. Conclusion: This stufy described the patterns of use of pain medications among older adults with cardiovascular disease. Careful selection of appropriate pain medications based on different clinical parameters is very essential to avoid prescribing inappropriate therapy that can lead to patient harm.